2022
DOI: 10.3389/fpls.2022.968514
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous silicon alleviates the adverse effects of cinnamic acid-induced autotoxicity stress on cucumber seedling growth

Abstract: Autotoxicity is a key factor that leads to obstacles in continuous cropping systems. Although Si is known to improve plant resistance to biotic and abiotic stresses, little is known about its role in regulating leaf water status, mineral nutrients, nitrogen metabolism, and root morphology of cucumber under autotoxicity stress. Here, we used cucumber seeds (Cucumis sativus L. cv. “Xinchun No. 4”) to evaluate how exogenous Si (1 mmol L−1) affected the leaf water status, mineral nutrient uptake, N metabolism-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Phloridzin lacks only one beta-D-glucopyranosyloxy group compared with Phloretin [ 40 ]. Replant stress inhibits the secretion of phloridzin by roots and promotes the secretion of phloridzin.…”
Section: Discussionmentioning
confidence: 99%
“…Phloridzin lacks only one beta-D-glucopyranosyloxy group compared with Phloretin [ 40 ]. Replant stress inhibits the secretion of phloridzin by roots and promotes the secretion of phloridzin.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that flavonoids secreted by leguminous plants contribute to nitrogen fixation, and carboxylates to phosphorus acquisition [ 43 , 44 ]. Furthermore, allelopathic autotoxicity occurs due to some chemicals secreted by C. sativus itself, such as cinnamic acid [ 45 , 46 ]. In our study, no significant differences were found in all growth response variables in the G. max neighbor or intraspecific competition treatments compared with solitary growing conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous cropping is the practice of planting the same crop or family on the same plot of land for many years. This can result in poor plant growth and development, smaller yellow leaves, increased disease, reduced crop quality, and lower yield ( Lyu et al., 2022 ). In recent decades, experts worldwide have begun to use crop science and ecology to study the barriers to continuous cropping at greater depths.…”
Section: Introductionmentioning
confidence: 99%